Исследование уровня маркеров функционального состояния сосудистой системы в острый период аневризматического субарахноидального кровоизлияния - Глоба, М.В.; Васильева, И.Г.; Чопик, Н.Г.; Сницар, Н.Д. (Таврический медико-биологический вестник, 2012)
У 26 хворих з аневризматичним субарахноїдальним крововиливом досліджували рівень аутоантитіл до антигенів ендотелію судин (с-ANCA – anti-neutrophil cytoplasmic antibody; NOS – нітрідоксидсинтаза; РАРР-А – білок, цинк-утримуюча матрична металопротеїназа; плазміноген/ ангіостатин; колаген), а також тромбоцитів (TrM-03). У всіх хворих показники аутоантитіл відрізнялись від групи контролю. Гіперпродукція переважно стосувалась антитіл до РАРР-А та NOS. Аномально низький рівень аутоантитіл реєструвався до антигенів TrM-03 та плазміногену/ангіостатину. У осіб з тяжким перебігом захворювання відзначались знижені рівні середньої імунореактивності організму. The level of autoantibodies to antigens of platelets (TrM-03) and vessels endothelium antigens (с-ANCA – anti-neutrophil cytoplasmic antibody; NOS – nitric oxide synthase; РАРР-А – Pregnancy-Associated Plasma protein, plasminogen/angoistatin, collagen) was determined in 26 patients with aneurysmal subarachnoid haemorrhage . The indicators of autoantibodies in all the patients were different from the ones in the control group. Hyperproduction of antibodies was mainly related to РАРР-А and NOS. Abnormally low autoantibody levels were registered to TrM-03 and plasminogen-angoistatin antigens. Reduced indices of mean immunoreactivity were observed in patients in grave condition.